PROJE FİNANSMANINDA TEMİNAT OLARAK ÜST HAKKI İPOTEĞİ - (:unkn) unknown (My University, 2018)
Üst hakkı, sahibine başkasına ait bir arazinin altında veya üstündeinşaat yaparak veya arazide mevcut olan bir inşaatı muhafaza ederek onamalik olma yetkisi veren bir irtifak hakkıdır. Üst hakkı, arazi malikinearazinin mülkiyetini kaybetmeden araziden finansal kaynak sağlamaimkânı verirken; üst hakkı sahibine de araziyi satın almadan arazi üze-rindeki yapının maliki olma yetkisi vermektedir. Bu özellikleri nedeniy-le, üst hakkının tarafların ekonomik çıkarlarına hizmet ettiği kabul edilir.Ülkemizde son yıllarda gerçekleştirilen ve büyük kaynak ihtiyacıgerektiren alt yapı, enerji ve sağlık konulu projelerde üst hakkı ile sıklık-la karşılaşılmaktadır. Bu projelerin hayata geçirilmesi için kullanılanYap İşlet Devret modelinin düzgün işlemesi için en uygun yol üst hak-kından yararlanılmasıdır.Ülkemizde büyük kaynak ihtiyacı gerektiren tüm projeler proje fi-nansmanı ile gerçekleştirilmektedir. Uzun dönemli finansal borçlanmasağlayan, özellikleri nedeniyle klasik kredilerden ayrılan ve finansalmühendislik modellerinden biri olarak kabul edilen proje finansmanı içinüst hakkının ekonomik değeri önem arz eder. Bu nedenle, bağımsız vesürekli nitelikte olan ve Tapu Siciline taşınmaz olarak kaydedilen üst

Right of construction is an easement right providing the holder with the right to construct and assume the title of a building below or over the land owned by another entity. While offering the land owner an opportunity to raise financial resources out of the land without losing its title, the right of construction gives its holder the right to own a building without buying a land. Due to its such advantages, the right of construc- tion is deemed to serve economic benefits of the Parties. The right of construction is a frequently encountered issue in high costing infrastructure, power or medical projects realized in Turkey re- cently. For the purposes of constructing such projects and sound functi- oning of the Build, Operate, Transfer Model, the most appropriate mo- del is the one that benefits from the right of construction. All high cost projects are funded by means of project financing. The economic value of the right of construction is very important for the project financing which provides the beneficiary with a long term finan- cial loan and is distinguished from conventional loans due to its nature in addition to being considered to be one of financial engineering mo- dels. Because of this, establishing on the right of construction, being an substantive and permanent right, a mortgage in favor of the project fi- nancing creditors is a situated practice. In this study, we shall focus on the issues which affect the security value of the right of construction mortgage, being an essential security of project financing. We must par- ticularly state that we shall refer to the right of construction, project financing and the relation between loan and security in our study suffi- ciently to serve the purposes of our study.
RIGHT OF CONSTRUCTION (SURFACE RIGHT) AS COLLATERAL IN PROJECT FINANCE
Keywords: Hukuk